Creativity in drawing: A study among high and low spatial learners / Meor Muhammad Aazim Mohd Ghazalli - Mohd Ghazalli, Meor Muhammad Aazim (Faculty of Education, 2014)
In Malaysia, drawing is a compulsory subtopic in Visual Art Education subject. A study was conducted in order to identify the creativity in drawing among High or Low Spatial Learners. This study also examined the relationship between High and Low Spatial Learners in terms of students’ genders. Furthermore, this study also identified the relationship between drawing creativities among the genders and measuring students drawing creativity using Torrance Test of Creative Thinking (TTCT). The present study adopted qualitative method where data were obtained through Drawing Test and Visual Spatial Test (Newton & Bristol, 2009). The numbers of samples involved in this study were 70. The students were all Form 3 students at Sek. Men. Keb. Alam Megah, Shah Alam. These students were selected randomly from their class name list. Findings of the study revealed that majority of the students were High Spatial Learners but only reached Average Level on their drawing test. It was found that the drawing ability and gender factors were not statically related. The data obtained from students’ drawing revealed that most students either male or female were High Spatial Learners and did not fit the criteria of TTCT in terms of creativity. They were only at Average Level in the Drawing Test. Hence, several implication and recommendations were outlined as to enhance creativity among High and Low Spatial Learners.